A 78-joints ultrasonographic assessment is associated with clinical assessments and is highly responsive to improvement in a longitudinal study of patients with rheumatoid arthritis starting adalimumab treatment. Issue 7 (14th May 2010) - Hammer, Hilde Berner; Sveinsson, Margareth; Kongtorp, Anne Katrine; Kvien, Tore K
Abstract : Objectives: To examine associations between ultrasonography (US) assessments (B-mode (BM) and power Doppler (PD)) of a large number of joints and traditional assessments of disease activity, and to examine the sensitivity to change of the US scores and clinical measures in patients with rheumatoid arthritis (RA). Methods: Twenty patients with RA initiating adalimumab treatment were examined at baseline and after 1, 3, 6 and 12 months with US (BM and PD) using an Outcome Measures in Rheumatoid Arthritis Clinical Trial semiquantitative scoring (0–3) of 78 joints as well as assessment of clinical and laboratory variables with calculation of composite indexes. Results: The US scores were associated with composite scores as well as clinical and laboratory variables (r=0.41–0.84, p<0.05–0.001 at 12-months' follow-up). Compared with clinical assessments, US detected higher numbers of inflamed joints. The US scores decreased after 1 and 3 months (p<0.005) and PD showed the highest percentage improvement. Both BM and PD had high standardised response means throughout the study (−0.83 to −1.27), of similar magnitude to composite indexes, but higher than the clinical and laboratory variables. Conclusions: The comprehensive US assessments were associated with clinical and laboratory variables of disease activity and were highly sensitive to change during treatment with biological agents.